Association between Long-term Exposure to Ambient Air Pollution and Myocardial Fibrosis Assessed with Cardiac MRI - Du Plessis, Jacques; DesRoche, Chloe; Delaney, Scott; Nethery, Rachel C; Hong, Rachel; Thavendiranathan, Paaladinesh; Ross, Heather; Castillo, Felipe; Hanneman, Kate (Radiology, 2025)
Background Poor air quality is associated with cardiovascular morbidity. However, the underlying pathophysiologic mechanisms are unclear. Purpose To determine the relationship between long-term exposure to ambient fine particulate matter with 2.5-µm or smaller aerodynamic diameter (PM ) and the extent of diffuse myocardial fibrosis quantified with cardiac MRI. Materials and Methods In this single-center retrospective study, patients with dilated cardiomyopathy (DCM) or controls with normal cardiac MRI findings were included (January 2018 to December 2022). Diffuse myocardial fibrosis was quantified using cardiac MRI native T1 mapping scores. Residence-specific ambient PM concentration was assessed as the mean of daily exposure concentration in the year before cardiac MRI using direct measurements from the nearest monitoring station. Multivariable models were adjusted for clinically relevant covariates. Results A total of 694 patients (mean age, 47 years ± 16 [SD]; 443 men; 493 with DCM, 201 controls) were included. In multivariable models, each 1-µg/m increase in 1-year mean PM exposure was associated with a 0.30 higher native T1 score in patients with DCM (adjusted β coefficient: 0.30; 95% CI: 0.13, 0.47; < .001) and 0.27 higher native T1 score in controls (adjusted β coefficient: 0.27; 95% CI: 0.04, 0.51; = .02). For absolute values, each 1-µg/m increase in 1-year mean PM exposure was associated with 9.1 msec higher native T1 at 1.5 T (β coefficient: 9.1; 95% CI: 2.04, 15.97; = .01) and 12.1 msec higher native T1 at 3 T (β coefficient: 12.1; 95% CI: 5.74, 18.52; < .001). Stratified models indicated the largest effect sizes for the association of PM exposure with native T1 scores in women (β coefficient: 0.49; 95% CI: 0.23, 0.76; < .001), smokers (β coefficient: 0.43; 95% CI: 0.02, 0.84; = .04), and patients with hypertension (β coefficient: 0.48; 95% CI: 0.16, 0.80; = .004). Conclusion Higher long-term exposure to ambient fine particulate air pollution is associated with greater diffuse myocardial fibrosis at cardiac MRI native T1 mapping in patients with DCM and healthy controls. © RSNA, 2025 See also the editorial by Vigneault in this issue.